LEVERAGE UKURAN PERUSAHAAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - Yulimtinan, Zalfa; Atiningsih, Suci (Balance : Jurnal Akuntansi dan Bisnis, 2021)
The purpose of this study if determine the effect of leverage, firm size and sales growth on firm value with profitability as intervening variable. The population in this study are automotive sector and metals sector listed on the Indonesia Stock Exchange in the 2015-2019 period using a purposive sampling method, 27 companies were selected in the sample. Analysis of the data used is the analysis of Partial Least Square (PLS) which is assisted with smartPLS 3.0 software. Based on the result of testing the data shows that leverage, firm size and sales growth have a positive effect on profitability. But leverage, firm size and sales growth have not effect on firm value. Profitability has a positive effect on firm value. Profitability is able to mediate the effect of leverage, firm size and sales growth on firm value.